Implementasi Pembelajaran PAI dalam Pembentukan Karakter Religius Peserta Didik di SMP Muhammadiyah 48 Medan - Ulfah, Syarifah Widya; Nurfadillah, Ainaya; Amanda, Fitry; Nurhikmah, Rizky Arafani (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
The development of science and technology has had a negative impact on the character of a nation. To address this impact, it is necessary to implement character education in educational institutions. This study aims to determine how Islamic Religious Education (PAI) is implemented in shaping the religious character of students at SMP Muhammadiyah 48 Medan, along with the supporting and inhibiting factors. This research is a type of field research with a qualitative descriptive approach. Data analysis is carried out by selecting, collecting, analyzing, and then drawing conclusions from the obtained data. The results of the study show that the teaching of Islamic Religious Education (PAI) at SMP Muhammadiyah 48 Medan in shaping the religious character of students is implemented through various school programs, including self-development, application in subjects, and integration into the school culture through 5S activities and several other activities. Supporting factors in this implementation include adequate facilities and infrastructure, supportive media that can help educators guide students in carrying out religious activities, the caring and togetherness attitude of educators in shaping students' characters, and support from the surrounding school environment. Meanwhile, inhibiting factors include unsupportive social interactions, family backgrounds and environments, the lack of religious role models for students at home, and the lack of religious awareness among students.